2023
DOI: 10.3390/insects14050430
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Lethal Effects of Pirimiphos-Methyl Are Expressed to Different Levels in Wings of Three Stored-Product Coleopterans: A Geometric Morphometrics Investigation

Abstract: Tenebrio molitor L. (Coleoptera: Tenebrionidae), Prostephanus truncatus (Horn), and Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) are noxious insect pests of grains in storages. Pirimiphos-methyl is widely used to protect grains at the post-harvest stage. However, the sub-lethal impact of this active ingredient on the offspring of all three coleopterans remains unknown. Thus, mated females of each species were exposed separately to pirimiphos-methyl at short exposures (30 min, 3, 5, 8, 16, 24, and 36 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The findings agreed with results of our study about sensitivity of T. granarium females to pirimiphos‐methyl. Nevertheless, a recent study showed inverse results where males of Tenebrio molitor L. (Coleoptera: Tenebrionidae) derived from females treated with pirimiphos‐methyl at sublethal exposures were more sensitive than females 30 . Therefore, the response of sexes of coleopterans to an insecticide is likely to be species‐dependent rather than a general trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings agreed with results of our study about sensitivity of T. granarium females to pirimiphos‐methyl. Nevertheless, a recent study showed inverse results where males of Tenebrio molitor L. (Coleoptera: Tenebrionidae) derived from females treated with pirimiphos‐methyl at sublethal exposures were more sensitive than females 30 . Therefore, the response of sexes of coleopterans to an insecticide is likely to be species‐dependent rather than a general trend.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the lethal effects of insecticides on storage pests, they exhibit sublethal effects that can negatively affect several biological and behavioral traits of insects 27–30 . Sublethal effects of insecticides are related to aggressive behavior, courtship, fecundity, longevity, sex ratio, mobility, lifespan, fertility, and morphology, among others 30–35 . For instance, successful copulations of Sitophilus oryzae (L.) (Coleoptera: Curculionidae) were reduced after exposure of both sexes to sublethal doses of pyrethrins 36 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides inducing mortality in storage pests, synthetic pesticides also induce sublethal effects that can influence the biology and behavioral characteristics of insects [ 18 , 19 ]. Some of the sublethal effects include aggressive behavior and a negative impact on courtship, lifespan, fecundity, fertility, locomotion, and morphology [ 20 , 21 , 22 ]. Insects have developed a range of behavioral reactions to insecticidal substances, leading to their reduced efficacy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%